Design and fabrication of biomaterial-based electronic and opto-electronic devices - WAHAB ABDUL (The Graduate School, Ajou University, 2024)
This thesis discusses the electronic and optoelectronic applications of melanin and silk biomaterials. Silk and melanin have a wide range of applications in fields like soft robotics, bioelectronics, wearable electronics and optoelectronics. This work comprised fabrication along with characterization of melanin particles incorporated in silk hydrogel films. A novel, self- healable and stretchable optoelectronic skin (OE-skin) is synthesized using melanin/silk that is photo-responsive in nature. Characteristics such as stretchability and humidity-dependent conductivity of OE-skin resulted in the fabrication of different sensory applications, for example, humidity and strain sensors. A Melanin/Silk photodetector is fabricated by joining it with p-Si. This photodetector can sense light patterns and it is also skin attachable. Melanin/silk thin films are also fabricated and utilized to create a transparent memristor and an organic electrochemical transistor (OECT) with a high on/off ratio. Both devices were implemented to obtain inhibitory (IPSP) and excitatory (EPSC) synaptic response with pair pulse facilitation (PPF). The first project deals with optoelectronic skins (OE-skin) which are of pivotal importance in robotics and human- machine communications. Here we present an implementation of OE-skin using silk protein and melanin nanoparticles that possess functionalities of the human skin along with photo-responsive characteristics. The fabricated OE-skin is stretchable, conductive, photo-responsive, and self- healable. Free radicals present in the melanin nanoparticles are activated at high humidity which ultimately increases the photoconductivity of OE-skin. On the other hand, Ca2+ ions capture water molecules from the environment that cause stretchability and self-healing in silk/melanin hydrogel layers. OE-skin exhibited an enhanced electrical conductivity upon increasing the humidity and under laser light illumination. These sensing capabilities of OE-skin have been employed to realize multiple sensors such as strain, humidity, and photoconductive sensors. The study suggested that our OE-skin provides a new outlook to the field of prosthetics and skin-attachable devices. In the second project, we fabricated a semiconducting layer by inserting melanin nanoparticles in silk hydrogel. The ionic conductivity of melanin nanoparticles is activated by water-rich silk hydrogel. A biomaterial-silicon junction is formed as Melanin/Silk and p-Si are joined to form a photodetector. The observed charge accumulation/transport behavior at the melanin NP-silk/p-Si junction is associated with the ionic conductive state of the melanin NP-silk composite. The Melanin NP-Silk semiconductor layer is printed on a p-Si substrate that exhibits photoresponse with illumination under different wavelengths. This photodetector when attached with an Ag nanowires incorporated silk layer can be attached with skin. The photo-responsive biomaterial-Si semiconductor junction using light as a stimulus offers a bio-friendly and versatile platform for artificial electronic skin/tissue. In the third project, we incorporated melanin in a silk solution and fabricated a melanin-silk thin film that has a lower bandgap in the range of wide bandgap semiconductors. UV-Vis absorbance results suggest a peak shift towards a higher wavelength and a significant decrease in bandgap as melanin particles are added to the silk matrix. Depending upon applied voltage and frequency, Capacitance-voltage (C-V) curves reveal three specific regions namely inversion, depletion, and accumulation similar to previous reports of biomaterials. The thin film is employed in the construction of an Ag/mel./silk/Au memristor and a biomaterial-based organic electrochemical transistor (OECT) with a high on/off ratio. Moreover, both devices manifest memory storage capabilities as represented by synaptic operation under microsecond pulses. Ag/Mel.-Silk/Au memristor unveils high-performing resistive switching with a low operating voltage and excellent repeatability.
학위논문(박사)--에너지시스템학과,2024. 2
Keywords: Applied Physics